The Utility of Electrochemical Systems in Microbial Degradation of Polycyclic Aromatic Hydrocarbons: Discourse, Diversity and Design - Hao, Da-Cheng; Li, Xiao-Jing; Xiao, Pei-Gen; Wang, Lian-Feng (Frontiers in Microbiology, 2020)
Polycyclic aromatic hydrocarbons (PAHs), especially high molecular weight (HMW) PAHs, are carcinogenic and mutagenic organic compounds that are difficult to degrade. Microbial remediation is a popular method for the PAH treatment in diverse environment media such as soil and sediment, etc. However, microbial remediation technology has many disadvantages, while the phytoremediation of PAH also has no ideal effect and cost performance. An emerging solution is to use microbial electrochemical system, in which microorganisms, electrode materials with optimized performance and devices with optimized design are combined flexibly to ensure the PAH removal and avoid the defects of traditional bioremediation. Based on the extensive investigation of recent literature, this paper summarizes and comments on the research progress of PAH removal by microbial electrochemical system of diversified design. Various combinations of microorganisms and electrochemistry can be adopted, though the microbial fuel cells (MFCs) predominate over other approaches. First, the electrochemical biodegradation of HMW PAHs is reviewed, and the removal performance of PAHs in different system configurations is compared. Low MW PAHs can be useful co-metabolic substrates in HMW PAH degradation. Carbon nanomaterials, bentonite, and iron showed their utility in anode modification and the subsequent PAH eradication. In MFC configuration, more attention has been paid to multi-anode design and enhancing mass transfer, and other clever designs are also proposed, especially that the combined use of phytoremediation could be an eco-friendly and sustainable approach. The rational use of methanol, some surfactants and biochar increased the PAH removal in MFC. The HMW PAH removal efficiency and the total production of electricity were generally nonlinear. Importantly, both bacteria and archaea with increased/decreased abundance are identified, providing a better scenario of PAH removal in MFC. Exoelectrogens and PAH degraders are partially overlapping, but the exact functional mechanisms of interaction network are still elusive. In order to optimize the efficacy of functional community, the anode modification should be further explored. More advanced techniques (such as omics technology, photoelectrocatalysis and nanotechnology) and novel electrode materials should be considered in the future experiment design to improve the power/current density and PAH biodegradation rate.